Moderated Mediation Mechanism to Determine the Effect of Gender Heterogeneity on Green Purchasing Intention: From the Perspective of Residents’ Values - Yang, Xianchuan; Kittikowit, Santhaya; Noparumpa, Tim; Jiang, Jiayun; Chen, Shih-Chih (Frontiers in Psychology, 2022)
This study determines gender differences in the generation logic for green purchasing intention within the framework of bounded morality and bounded self-interest and determines the causes of the attitude-behavior gap from a new perspective. Empirical analysis of 977 sample data points is used to test the influencing mechanism of gender heterogeneity on green purchasing intention through altruistic values and egoistic values. Meanwhile, the moderated mediation effects are also analyzed. The results show that gender heterogeneity negatively affects altruistic values and positively affects egoistic values for females as reference group. The mediation effect of altruistic values and egoistic values is significant, there are significant gender differences in the formation of values and green purchase intention. As expected, females demonstrate higher levels of pro-environmental intention than males. Media exposure significantly moderates the mediation models. It negatively moderates the mediation effect of altruistic values and positively moderates the mediation effect of egoistic values. The results reveal the complex formation mechanism for green purchasing intention. It can conclude that the gender differences in terms of green purchasing, the different guiding role of dual values and the moderated mechanism of media exposure are key to elements in accurate guidance of green consumption and the effective modification of the attitude-behavior gap.